2005
DOI: 10.1038/nbt1131
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequence of the chlorinated compound–respiring bacterium Dehalococcoides species strain CBDB1

Abstract: Dehalococcoides species are strictly anaerobic bacteria, which catabolize many of the most toxic and persistent chlorinated aromatics and aliphatics by reductive dechlorination and are used for in situ bioremediation of contaminated sites. Our sequencing of the complete 1,395,502 base pair genome of Dehalococcoides strain CBDB1 has revealed the presence of 32 reductive-dehalogenase-homologous (rdh) genes, possibly conferring on the bacteria an immense dehalogenating potential. Most rdh genes were associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
384
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 279 publications
(397 citation statements)
references
References 34 publications
10
384
0
1
Order By: Relevance
“…The upstream region of the RDase gene mbrA (dceA6) is a DNA-binding response regulator, whereas the 5 0 region of the dceA7 gene shares high identity with the SAM domain-containing protein as shown in strain 195. The transcription level of the mbrA gene is lower compared with some other known RDase genes such as the tceA gene, which is possibly due to the tight regulation of transcription by the upstream DNA-binding response regulator protein (Wagner et al, 2009;Kube et al, 2005). The upstream regions of the RDase genes have attracted much interest recently with current genome sequencing projects (Kube et al, 2005;Seshadri et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The upstream region of the RDase gene mbrA (dceA6) is a DNA-binding response regulator, whereas the 5 0 region of the dceA7 gene shares high identity with the SAM domain-containing protein as shown in strain 195. The transcription level of the mbrA gene is lower compared with some other known RDase genes such as the tceA gene, which is possibly due to the tight regulation of transcription by the upstream DNA-binding response regulator protein (Wagner et al, 2009;Kube et al, 2005). The upstream regions of the RDase genes have attracted much interest recently with current genome sequencing projects (Kube et al, 2005;Seshadri et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be speculated that at mesophilic temperatures, besides cbrA and cbdbA1624, some other rdh genes contribute significantly to the metabolic activity. Complex transcriptional responses to various chlorinated compounds were previously reported for Dehalococcoides isolates and cocultures (16,44,45) and were predicted to be tightly regulated by two-component and/or MarR-type regulators (29,35). The majority of rdh genes detected with T-RFLP and sequencing analysis were similar to those of strain CBDB1, which are located close to MarR-type regulators.…”
Section: Discussionmentioning
confidence: 50%
“…These regulators were shown to have "phenolic-sensing capabilities" (47) and to activate or repress gene expression during aromaticcompound degradation (43) in several other bacteria. It has been suggested that the possibly MarR-regulated rdhA genes might play an important role in haloaromatic compound degradation pathways (29). Since these genes could be detected both in situ and in sediment microcosms, it is tempting to speculate that they carry a great potential to be used as biomarkers of anaerobic haloaromatic-compound degradation capacity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations